The Relationship of Family Support with Self-Esteem Level in People Living with HIV/AIDS (PLWHA) in Sadar Hati Foundation Malang - setyoadi, setyoadi; Supriati, Lilik; Selvitriana, Dwi Retno (Journal Nursing Care and Biomolecular, 2018)
People who have been infected with the HIV virus (PLWHA) faced with the social problem of stigma and discrimination from the community and the surrounding environment PLWHA. It will affect the level of self-esteem of PLWHA. Self-steem in HIV positive is very important so that they do not fall under stress condition that can affect their health. One of the factors that may affect the level of self-esteem is family support. The purpose of this study was to analyze the relationship between family support with the level of self-esteem in People Living with HIV/AIDS (PLWHA). The design of this study used observational analytic with cross sectional method. The population of this sudy constitude of 50 HIV positive who are in assisted Sadar Hati Foundation Malang. Purposive sampling techniques was used and sample obtained as many as 44 people. The level of self-esteem was assessed using Rosenbergâs self-esteem scale and family support was assesed using questionnaire. Spearman Rank test results obtained by p value = 0.000 (p < 0.05) and the coefficient of correlation (r) = 0.545. It can be concluded that there was a significant relationship between family support with a level of self-esteem in People Living with HIV/AIDS (PLWHA) in Sadar Hati Foundation Malang. The line of both variables have positive (+) sign which means that the higher family support is given, the higher the self-esteem of PLWHA.